Hypokalaemia: Clinical Signifi cance and Role in the Mechanisms Underlying Cardiac Arrhythmogenesis - О. Е. Osadchii (Кубанский научный медицинский вестник, 2019)
Hypokalaemia is the most common electrolyte abnormality seen in cardiac patients, which represents a side effect of diuretic therapy or results from the overactivation of the renin-angiotensinaldosterone system and the sympathetic nervous system in heart failure. Hypokalaemia is known to contribute to an increased risk of ventricular arrhythmias whose mechanism is based on the dynamic interplay of the provocative trigger and the vulnerable substrate. A premature ectopic impulse acts as a provocative trigger, whereas the vulnerable substrate is created by the structural and functional myocardial changes that favour the impulse circulation within a closed conducting pathway, thus perpetuating the re-entrant activation. The premature ectopic impulse that serves as the initiating event for arrhythmia can be generated due to abnormal automaticity or triggered activity. Hypokalaemia facilitates abnormal automaticity by increasing the rate of spontaneous diastolic depolarisation in Purkinje fi bres, which then start to exhibit pacemaker activity that interferes with the regular activations set by the sinoatrial node. The triggered activity is attributable to the early and delayed afterdepolarisations in cardiac myocytes. The early afterdepolarisations are typically precipitated by an excessive lengthening of the cardiac action potential duration that results from the inhibition of the repolarising K+ currents in the setting of hypokalaemia. The delayed afterdepolarisations are related to calcium overload in cardiac cells, which is provoked by hypokalaemia via inhibition of the Na+-K+ ATPase on myocyte sarcolemma. This translates to the increased intracellular Na+ levels, which in turn activate the reverse mode of the Na+-Ca2+ exchange, leading to increased cytosolic Ca2+ concentration. With regard to creating a vulnerable substrate for re-entry, hypokalaemia is known to induce a non-uniform increase in the action potential duration in different myocardial regions, which amplifi es spatial heterogeneities in the recovery of ventricular excitability during the fi nal repolarisation phase. This sets favourable conditions for a unidirectional conduction block upon premature ectopic activation, which initiates the impulse propagation around a small area of refractory cardiac tissue. In addition, hypokalaemia slows cardiac conduction by inducing hyperpolarisation of the myocyte sarcolemma that results in markedly increased excitation threshold. The induced conduction delay in the re-entrant circuit then allows suffi cient time for recovery from refractoriness in the cardiac cells ahead of the excitation wavefront, which sustains re-entrant activation. The risk of ventricular tachyarrhythmia becomes particularly high when hypokalaemia is combined with the administration of cardiac glycosides or class III antiarrhythmic agents.